Anti-TNFR1 targeting in humanized mice ameliorates disease in a model of multiple sclerosis - Williams-Fairless, Sarah K.; Fairless, Richard; Pichi, Kira; Diem, Ricarda (Scientific reports, 2018)
Tumour necrosis factor (TNF) signalling is mediated via two receptors, TNF-receptor 1 (TNFR1) and TNF-receptor 2 (TNFR2), which work antithetically to balance CNS immune responses involved in autoimmune diseases such as multiple sclerosis. To determine the therapeutic potential of selectively inhibiting TNFR1 in mice with experimental autoimmune encephalomyelitis, we used chimeric human/mouse TNFR1 knock-in mice allowing the evaluation of antagonistic anti-human TNFR1 antibody efficacy. Treatment of mice after onset of disease with ATROSAB resulted in a robust amelioration of disease severity, correlating with reduced central nervous system immune cell infiltration. Long-term efficacy of treatment was achieved by treatment with the parental mouse anti-human TNFR1 antibody, H398, and extended by subsequent re-treatment of mice following relapse. Our data support the hypothesis that anti-TNFR1 therapy restricts immune cell infiltration across the blood-brain barrier through the down-regulation of TNF-induced adhesion molecules, rather than altering immune cell composition or activity. Collectively, we demonstrate the potential for anti-human TNFR1 therapies to effectively modulate immune responses in autoimmune disease.